THE BEINGS WITH MASK IN NASCA ICONOGRAPHY - Kindt, Petra (2009)
In this article there is discussed the identification of the personage that Seler names “a demoniacal cat”, and who would have an iconographic development that initiates with the simple representation of a feline up to coming to a winged being. From a detailed analysis of his attributes one raises that his multiple combinations are inside a temporary dimension possibly tied to the agricultural cycle.